Noninvasive Monitoring of Inflammatory Processes by Myeloid Cell-Directed PET Tracers in an Experimental Severe Acute Respiratory Syndrome Coronavirus 2 Infection Model - Stammes, Marieke A; Koopman, Gerrit; Wagner, Teresa R; Traenkle, Bjoern; Kaiser, Philipp D; Mooij, Petra; van der Werff, Nicole; Acar, Roja Fidel; Böszörményi, Kinga P; Blaess, Simone; Pezzana, Stefania; Reischl, Gerald; et al. (Society of Nuclear Medicine Inc., 2025)
Monitoring the presence and distribution of distinct immune cell populations is key in deciphering immunopathologic disease mechanisms. Considering the crucial role of myeloid cells in provoking hyperinflammatory responses associated with coronavirus disease 2019, a camelid-derived single-domain antibody specifically recognizing human signal-regulatory protein-α (SIRPα) as a biomarker for myeloid cells has been generated and radiolabeled with 64Cu, that is, [64Cu]copper-SIRPα-nanobody ([64Cu]Cu-SIRPα-Nb), for in vivo PET imaging. In this study, this PET tracer was used and validated to monitor the temporal dynamics of inflammatory processes during severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in nonhuman primates. For further validation, the signal of [64Cu]Cu-SIRPα-Nb was compared with the signal of TSPO-targeting [18F]fluorine-N,N-diethyl-2-(2-(4-(2-fluoroethoxy)phenyl)-5,7-dimethylpyrazolo[1,5a]pyrimidin-3-yl)acetamide ([18F]F-DPA714). Methods: Six cynomolgus macaques (Macaca fascicularis) were experimentally infected with SARS-CoV-2 and subsequently monitored for 7 wk. We performed a baseline [64Cu]Cu-SIRPα-Nb PET/CT before infection, followed by repetitive PET/CT on days 3, 10, 24, and 52 after infection covering the head, thorax, and abdominal region. Of the 6 macaques, 3 underwent additional TSPO-targeting [18F]F-DPA714 PET/CT investigations at baseline and at days 2, 9, 23, and 51 after infection. Tracheal and nasal swabs were taken to monitor the course of infection, and changes in blood count and inflammatory mediators in the periphery blood were monitored. Results: Detection of subgenomic SARS-CoV-2 messenger RNA from tracheal and nasal swab samples confirmed viral infection of all animals. CT scans identified initial pulmonary lesions 2 days after infection. [64Cu]Cu-SIRPα-Nb PET/CT revealed increased tracer uptake in the mediastinal lymph nodes of all animals, but not in the lung lesions, 3 days after infection. [18F]F-DPA714 PET/CT showed increased uptake in both anatomically affected and unaffected lung tissues. The increased [64Cu]Cu-SIRPα-Nb uptake in the spleen and bone marrow of all animals was more pronounced 3 and 7 wk after infection. We detected individual differences in [64Cu]Cu-SIRPα-Nb uptake within the bone marrow and spleen, whereas [18F]F-DPA714 exhibited rather homogeneous uptake patterns. Conclusion: Our findings indicate that [64Cu]Cu-SIRPα-Nb is a versatile tool for quantitative monitoring of whole-body distribution, temporal distribution, and accumulation dynamics of myeloid cell subpopulations even in moderately inflamed tissues and affected lymphatic organs during SARS-CoV-2 infection.
Keywords: COVID-19; PET/CT; SIRPα; TSPO; monitoring of infection; nanobody; Radiology Nuclear Medicine and imaging; SDG 3 - Good Health and Well-being